THE EFFECTIVENESS OF SUPPORTIVE SELF CARE EDUCATION USING THE EDUCATION BOOKLET TOWARD THE ABILITY EARLY DETECTION OF HYPOGLYCEMIA AND HYPERGLYCEMIA OF DIABETES MELLITUS PATIENTS AT RSUD BIMA IN 2017 - Martiningsih Martiningsih; Rini Hendari; Ahmad D. Ahmad (Jurnal Kesehatan Prima, 2018)
Abstract: Diabetes Mellitus (DM) is a metabolic disorder caused by a disruption of insulin secretion or impaired insulin activity resulting in the occurrence of hyperglycemia and cells not getting enough glucose for energy. Hypoglycemia and Hyperglycemia in DM patients is an acute complication of DM that can occur repeatedly and can aggravate DM disease can even cause death. Prevalence of hypoglycemia is quite high, about 90% of patients receiving insulin therapy have experienced hypoglycemia. The high prevalence and the magnitude risk of hypoglycemia and severe hyperglycemia is closely relate to the behavior of DM patients in managing the disease, especially behavior and the ability in early detection of hypoglycemic conditions and hyperglycemia. The development of hypoglycemia and hyperglycemia in more severe circumstances can be prevented by increased ability to control blood glucose and early detection of hypoglycemia and hyperglycemia by enhancing early detection of risk factors or causes, interpretation of symptoms of hypoglycemia and early hyperglycemia so that more severe complications can be prevented. The purpose of this study is to analyze the The effectiveness of Supportive Self Care Education using the Educational Booklet toward the ability  Early Detection of Hypoglycemia and Hyperglycemia of Diabetes Mellitus Patients at RSUD Bima in 2017. This type of research is quantitative research using pre experiment design with two group pretest and posttest approach. Independent T test was used to analyse the data. The study had been conducted for 9 weeks, from September to October 2017. The results show that supportive self-care education with educational booklet increase the ability of  detection hypoglicemia and hyperglycemia that are indcated by the increasing ability of early detection of hypoglycemia and hyperglycemia in treatment group compared to group control (p = 0.000; α = 0.05). The findings are expected to improve nursing care in DM patients, as one of the independent interventions that can be done by nurses and to increase knowledge related to the concept of self-care education in nursing perspective based on self-care orem nursing theory and to be able to provide education with appropriate methods, prevent acute hypoglycemic and hyperglycemic emergencies.Keywords: Educational, Booklet, Hypoglicemia, Hyperglicemia.